The Unique and Shared Genetic and Environmental Contributions to Fear, Anger, and Sadness in Childhood. Issue 5 (16th July 2015) - Clifford, Sierra; Lemery‐Chalfant, Kathryn; Goldsmith, H. Hill
<x xml:space="preserve">Abstract</x> This study examined the extent to which subordinate dimensions of negative emotionality were genetically and environmentally distinct in a sample of 1, 316 twins (51% female, 85.8% Caucasian, primarily middle class, Mage = 7.87 years, SD = .93), recruited from Wisconsin hospital birth records between 1989 and 2004. Cholesky, independent pathway, and common pathway models were fitted for mother report, father report, and in‐home observation of temperament. Although findings support the use of negative emotionality, there were heritable aspects of anger and fear not explained by a common genetic factor, and shared environmental influences common to anger and sadness but not fear. Observed fear was independent from observed anger and sadness. Distinctions support specificity in measurement when considering implications for child development.